CRYSTAL STRUCTURE OF (E)-N'-((1H-PYRROL-2-YL)METHYLENE)-4-HYDROXYBENZOHYDRAZIDE - Ghodrat Mahmoudi; Sadegh Rostamnia; Guillermo Zaragoza; Iván Brito; Jonathan Cisterna; Alejandro Cárdenas (Journal of the Chilean Chemical Society, 2019)
The title compound corresponds to an enaminone E isomer in the solid state. X-ray structure shows that this crystallizes in the orthorrombic system, with space group Pna21 with 2 independent molecules in the asymmetric unit in a non-centrosymmetric setting. The CNNC unit forms dihedral angles of 5.9(3)/2.1(3); 19.7(3)/17.6(3)° with the pyrrole and phenol rings for molecules A and B respectively. The main differences between both molecules is the dihedral torsion between rings, their mean planes form dihedral angles of 25.45(15) and 15.38(15)° for the molecules A and B. In the asymmetric unit, molecules are linked by two weak N – H···O hydrogen bonds with set graph-motif